Nominalização e transitividade - Rezende, Letícia Marcondes [UNESP] (My University, 2010)
This text is part of a larger study that initially aimed at focusing the relation between nominalization and transitivity in the Portuguese Language. Based on A. Culioli´s Theory of the Enuntiative Operations, we started from a static and descriptive analysis of language, in which nominalization and transitivity have visibility, towards a study that takes into consideration the articulation between language and natural languages. This second approach diluted the specificity of these two grammatical questions and directed them to more abstract spaces of reflection and common to any grammatical problem, such as causality, differential propriety and the construction of notional domains.

Este texto apresenta um recorte de um estudo mais amplo que teve como preocupação inicial a relação entre nominalização e transitividade em língua portuguesa. Tendo como suporte teórico a Teoria das Operações Enunciativas de A. Culioli, caminhamos de uma análise estática e descritiva de língua na qual essas questões têm visibilidade para um estudo que levasse em consideração a articulação entre linguagem e línguas naturais. Esse segundo enfoque diluiu a especificidade dessas duas questões gramaticais e as direcionou para espaços de reflexão mais abstratos e comuns a qualquer problema gramatical tais como causalidade, propriedade diferencial e construção de domínios nocionais.
Nominalization and transitivity
Keywords: Causality; Differential propriety; Construction of notional domains; Transitivity; Nominalization; Causalidade; propriedade diferencial; construção de domínios nocionais; transitividade; nominalização